Role of postoperative radiotherapy in reducing ipsilateral recurrence in DCIS: An observational study of 1048 cases - Corradini, Stefanie; Pazos, Montserrat; Schönecker, Stephan; Reitz, Daniel; Niyazi, Maximilian; Ganswindt, Ute; Schrodi, Simone; Braun, Michael; Pölcher, Martin; Mahner, Sven; Harbeck, Nadia; Engel, Jutta; et al. (Radiation Oncology, 2018)
Background: The objective of the present study was to evaluate the effectiveness of postoperative radiotherapy after breast conserving surgery (BCS) in DCIS in a large patient population treated in clinical practice. Methods: Data were provided by the population-based Munich Cancer Registry. Between 1998 and 2014, 1048 female patients with diagnosis of DCIS and treated at two Breast Care Centres were included in this observational study. The effectiveness of postoperative radiotherapy and variables predicting the use of radiotherapy were retrospectively analysed. Results: After adjusting for age, tumour characteristics and therapies, Cox regression analysis for local recurrence-free survival identified RT as an independent predictor for improved local control (HR: 0.579; 95%CI: 0.384-0.872, p = 0.008). Ten-year cumulative incidence of in-breast recurrences was 20.0% following BCS, compared to 13.6% in patients receiving postoperative radiotherapy (p = 0.012). As an estimate for disease-specific survival, 10-year relative survival was 105.4% for patients receiving postoperative radiotherapy and 101.6% without radiotherapy. On multivariate analysis, postoperative radiotherapy was not associated with improved overall survival (HR 0.526; 95%CI: 0.263-1.052, p = 0.069). Over time, a significant increase of RT was registered: while 1998 only 42.9% of patients received postoperative radiotherapy, the proportion rose to 91.2% in 2014. Women aged < 50 years (OR: 2.559, 95%CI: 1.416-4.625, p < 0.001) or with negative hormone receptor status (OR: 2.625, 95%CI: 1.458-4.728, p = 0.001) or receiving endocrine therapy (OR: 1.762, 95%CI: 1.060-2.927, p = 0.029) were more likely to receive postoperative radiotherapy after BCS. Conclusions: In conclusion, this study provides insights regarding the adoption and treatment pattern of postoperative RT following BCS for DCIS in a large cohort reflecting "real-life" clinical practice in this setting. Postoperative RT was found to be associated with a reduced risk of ipsilateral recurrence and no survival benefit compared to observation alone.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Breast conserving surgery; Ductal carcinoma in situ; In-breast recurrence; Local control; Outcome; Radiotherapy; Survival